Preliminary study on crystallinity of rice husk ash reinforcement for metal matrix composite - Thiagarajan, Ganabpaty; Abdul Latif, Noradila; Mohd Joharudin, Nurul Farahin (FAZ Publishing, 2020)
Rice husk ash burned at high temperatures produce high silica content and its can be used as potential reinforcing agent that able to replace other conventional silica. This paper presents the preliminary study on crystallinity of rice husk silica that burning in high temperature. Crystallinity of rice husk silica was evaluated using the Origin software. Based on previous study on finding of rice husk ash in metal matrix composites (MMCs), the uses of rice husk ash improved the physical and mechanical properties of MMCs. This study was conducted until the preliminary stage of preparing aluminium chips and the rice husk silica that burned at 1000℃. As a result, the crystalline graph of rice husk silica by using x-ray diffraction (XRD) showed the narrow peak appeared in high intensity volume and the crystallinity of rice husk silica was 88.6%.